The Effectiveness and Safety of Tranexamic Acid in Orthotopic Liver Transplantation Clinical Practice: A Propensity Score Matched Cohort Study. Issue 7 (July 2017) - Badenoch, Adam; Sharma, Anand; Gower, Simon; Selzner, Markus; Srinivas, Coimbatore; Wąsowicz, Marcin; McCluskey, Stuart A.
Abstract : Background: Randomized trials have demonstrated the efficacy of tranexamic acid (TXA) in reducing blood loss and transfusion requirements during liver transplantation. However, clinical utilization is limited due to a perceived lack of generalizable effectiveness and concerns regarding its thromboembolic risks. The aim of this study was to describe the clinical use of TXA and to provide a pragmatic reappraisal of its effectiveness and safety. Methods: After ethics approval, data were collected from 1799 consecutive liver transplant recipients between January 1, 2002, and December 31, 2015, using retrospectively collected electronic databases. Propensity matching was used to account for confounders of transfusion and thrombotic risk. Exposure was defined as a total TXA dose greater than 10 mg/kg for 50% of the operative duration. Results: After propensity matching, 367 unique pairs were well balanced in terms of all measured covariates. In the matched pairs, patients exposed to TXA received less red blood cell (3 [0, 6] vs 4 [1, 7] P = 0.003) and frozen plasma (6 [2, 10] vs 6 [2, 12], P = 0.032) transfusions. There were no differences in thromboembolic events between the groups (22 [6.0%] vs 36 [9.8%]). Conclusions: TXA appears effective in reducing red blood cell transfusion requirements without increasing the risk of thromboembolic events across a wide variety of liver transplant recipients, including those at low risk of bleeding or high risk of thromboembolic complications. We did not detect evidence of an increased risk of thrombotic complications with TXA exposure. Abstract : The authors of this propensity score matched cohort study describe the effectiveness of tranexamic acid across a wide variety of liver transplant recipients, reducing red blood cell transfusion requirements, without increasing the risk of thromboembolic events. Supplemental digital content is available in the text.